Vitreous polyamines spermidine, putrescine, and spermine in human proliferative disorders of the retina. Issue 8 (24th July 2003) - Nicoletti, R; Venza, I; Ceci, G; Visalli, M; Teti, D; Reibaldi, A
Abstract : Background/aims: Many cytokines are involved in the pathogenesis of retinal proliferative diseases, but none has been shown to be related to a specific disorder. The aim of this study was to provide a selective marker of diabetes induced proliferative retinopathies. Methods: 10 vitreous samples from 10 subjects affected by quiescent proliferative diabetic retinopathy (PDR), 20 vitreous samples from 20 subjects affected by active PDR, and 15 samples from 15 patients with proliferative vitreoretinopathy (PVR) were studied. Samples from 18 patients with a macular hole (n = 8) or pucker (n = 10) served as controls. Vitreous samples were obtained via pars plana vitrectomy. The polyamines spermidine, putrescine, and spermine, vascular endothelial growth factor (VEGF), interleukin 8 (IL-8), and transforming growth factor 1β (TGF-1β) were measured by high performance liquid chromatography (HPLC) and enzyme linked immunosorbent assay (ELISA), and the correlation coefficients between the vitreous polyamine content and VEGF, IL-8, and TGF-1β levels were determined. Results: Spermidine and putrescine were expressed in normal vitreous, but spermine was not detectable. In all the test groups spermidine was 3–4 times higher than in control vitreous and putrescine was similarly lower. The spermine content was up to 15 times higher only in vitreous from patients affected by PDR. Correlation coefficients showed that the spermidine and putrescine level variations correlated with the VEGF and IL-8 content in the active PDR and PVR groups, but not in those with quiescent PDR patients, while spermine was correlated to these cytokines in PDR, but not in PVR groups. Conclusions: These data suggest a significant role for spermidine and putrescine as markers of proliferative diseases of the retina. The increase in spermine, restricted to diabetic states, may indicate that this polyamine is a unique and specific index of PDR.